Strategi Digital Marketing Untuk Meningkatkan Brand Awareness Melalui Platform Instagram & Tiktok Pada Amali Eatery - Sutina, Ratna Ramadanne; Awaliyah, Aza; Sulaeman, Eman (Politeknik Negeri Ambon, 2025)
Introduction: Digital marketing project, using the Capstone Project method to assist Small and Medium Enterprises (SMEs) in solving the problem of intense competition in the Food and Beverage (F&B) industry market in Bandung City through a real-case study. Amali Eatery is a restaurant and café established in 2023, located within an elite residential area in Bandung City. This project aimed to increase the engagement rate for Amali Eatery through a digital marketing strategy with content management based on the Instagram and TikTok social media platforms, as well as to provide actionable recommendations to increase brand awareness.Methods: Various digital marketing strategic interventions were implemented, including copywriting, content pillars, marketing mix, rebranding, social media advertising, and collaboration with a Key Opinion Leader (KOL).Results: The project results show a significant increase in several Key Performance Indicators (KPIs). The Instagram account’s Engagement Rate (ER) increased from 1.12% to 4.9%, while the TikTok account's ER increased from 0% to 4.0%. The growth in Instagram followers from 855 to 1,103, and TikTok followers increased from 1 to 185. Furthermore, customer insights indicated a rise in positive engagement and interaction with the content. This shows that implementing an integrated digital marketing strategy, which combines relevant organic content with paid amplification, has proven effective in enhancing Amali Eatery's brand awareness within a competitive market. Keyword: Digital Marketing, Brand Awareness, Engagement, Social Media, Amali Eatery